How the ghrelin receptor recognizes the acyl-modified orexigenic hormone - Shiimura, Yuki; Kojima, Masayasu; Sato, Takahiro (Frontiers in Molecular Neuroscience, 2025)
Ghrelin, discovered in 1999 as an endogenous ligand of the growth hormone secretagogue receptor (now known as the ghrelin receptor), is a peptide hormone with diverse physiological activities, such as stimulation of growth hormone release, increased appetite, fat accumulation, thermoregulation, and cardioprotection. As a distinctive feature, ghrelin needs to undergo octanoylation, a specific acyl modification, to exert its biological activities. Although the ghrelin receptor specifically recognizes this modification, the underlying molecular mechanism had remained unclear for decades. Recent advancements in structural biology have facilitated the elucidation of this recognition mechanism 25 years after ghrelin’s discovery. This review highlights the structural basis of ghrelin octanoylation, particularly emphasizing the mechanism by which the ghrelin receptor recognizes this acyl-modified hormone.